2016
DOI: 10.1007/s11547-016-0641-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tablet ultrasound for routine abdominal interventional procedures

Abstract: The novel tablet US was found to provide sufficient image quality for the majority of routine interventional procedures. Dedicated accessories and additional experience with this new generation US device may be needed to replace bulky high-end US systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similar experiences have been reported for the detection of vertebral fractures on plain spinal radiography ( Murata et al, 2020 ), the diagnosis of tuberculosis ( Lakhani and Sundaram, 2017 ), and the estimation of bone age ( Dedouit et al, 2015 ). More generally, different DL methods have been applied to biomedical image analysis ( Ierardi et al, 2016 ; Trimboli et al, 2018 ; Villanueva-Meyer et al, 2019 ) and successfully used with various imaging modalities, such as breast ( Kallenberg et al, 2016 ; Zanotel et al, 2018 ; Geras et al, 2019 ; Hickman et al, 2021 ) and cardiac imaging ( van Assen et al, 2020 ), MSCT ( Lerouge et al, 2015 ; Kooi et al, 2017 ; Hu et al, 2020 ), MRI ( Havaei et al, 2017 ; Ariji et al, 2019 ; Figure 2 ), as well as in interventional radiology ( Gurgitano et al, 2021 ). AI can also be helpful to quantify lung involvement and predict prognosis in patients with COVID-19 pneumonia ( Belfiore et al, 2020 ; Akram et al, 2021 ; Cappabianca et al, 2021 ), and Harmon et al (2020) recently found that a series of DL algorithms trained in a diverse multinational cohort of 1280 patients can achieve up to 90.8% accuracy, with 84% sensitivity and 93% specificity in detecting COVID-19 pneumonia on chest CT examinations of 1337 patients.…”
Section: Artificial Intelligence: Basic Conceptsmentioning
confidence: 99%
“…Similar experiences have been reported for the detection of vertebral fractures on plain spinal radiography ( Murata et al, 2020 ), the diagnosis of tuberculosis ( Lakhani and Sundaram, 2017 ), and the estimation of bone age ( Dedouit et al, 2015 ). More generally, different DL methods have been applied to biomedical image analysis ( Ierardi et al, 2016 ; Trimboli et al, 2018 ; Villanueva-Meyer et al, 2019 ) and successfully used with various imaging modalities, such as breast ( Kallenberg et al, 2016 ; Zanotel et al, 2018 ; Geras et al, 2019 ; Hickman et al, 2021 ) and cardiac imaging ( van Assen et al, 2020 ), MSCT ( Lerouge et al, 2015 ; Kooi et al, 2017 ; Hu et al, 2020 ), MRI ( Havaei et al, 2017 ; Ariji et al, 2019 ; Figure 2 ), as well as in interventional radiology ( Gurgitano et al, 2021 ). AI can also be helpful to quantify lung involvement and predict prognosis in patients with COVID-19 pneumonia ( Belfiore et al, 2020 ; Akram et al, 2021 ; Cappabianca et al, 2021 ), and Harmon et al (2020) recently found that a series of DL algorithms trained in a diverse multinational cohort of 1280 patients can achieve up to 90.8% accuracy, with 84% sensitivity and 93% specificity in detecting COVID-19 pneumonia on chest CT examinations of 1337 patients.…”
Section: Artificial Intelligence: Basic Conceptsmentioning
confidence: 99%
“…However, in recent years, advances in technology have enabled the development of medical devices that are more cost-effective, smaller and consume less power. Recently, considering diagnostic ultrasound (US) devices, pocket-sized mobile devices have become popular within the elds of obstetrics and gynecology [6,7], gastroenterology [8], cardiology [9], pulmonology [10], rheumatology [11] and emergency medicine [12]. Such devices are also expected to be critical equipment in rural areas and emerging economies [13].…”
Section: Page 3/12mentioning
confidence: 99%
“…Interventional radiologists use x-rays, computed tomography, magnetic resonance, or other imaging guidance to navigate small instruments, like catheters and needles, through blood vessels and organs to treat a variety of diseases. 1 , 2 Examples of treatments administered by interventional radiologists include angioplasty, biopsies, stenting, thrombolysis, embolization, and radiofrequency ablation. 1 , 3 , 4 , 5 , 6…”
Section: Introductionmentioning
confidence: 99%